Isometric hip strength impairments in patients with hip dysplasia are improved but not normalized 1 year after periacetabular osteotomy: a cohort study of 82 patients - Julie Sandell Jacobsen (Acta Orthopaedica, 2021)
Background and purpose — In patients with hip dysplasia, knowledge of hip muscle strength after periacetabular osteotomy is lacking. We investigated isometric hip muscle strength in patients with hip dysplasia, before and 1 year after periacetabular osteotomy, and compared this with healthy volunteers. Furthermore, we investigated whether pre- to post-surgical changes in self-reported pain and sporting function were associated with changes in isometric hip muscle strength. Patients and methods — Isometric hip muscle strength was assessed twice in 82 patients (11 men) with a mean age of 30 (SD 9) years, before and 1 year after surgery, and once in 50 healthy volunteers. Isometric hip muscle strength was assessed with a hand-held dynamometer. Copenhagen Hip and Groin Outcome Score was used to measure self-reported outcome. Results — Despite 1-year improvements in isometric hip flexion (0.1 Nm/kg; 95% CI 0.06–0.2) and abduction (0.1 Nm/kg; CI 0.02–0.2), the patients’ muscle strength was 13–34% lower than the strength of the healthy volunteers both pre- and post-surgery (p < 0.01). Moreover, changes in self-reported pain were associated with changes in hip flexion (13 points per Nm/kg; CI 1–26) and abduction (14 points per Nm/kg; CI 3–25), while changes in self-reported sporting function were associated with changes in hip extension (9 points per Nm/kg; CI 1–18). Interpretation — Isometric hip muscle strength is impaired in symptomatic dysplastic hips measured before periacetabular osteotomy. 1 year after surgery, isometric hip flexion and abduction strength had improved but muscle strength did not reach that of healthy volunteers.